Penerapan Sanksi Hukum terhadap Pelaku Ekspolitasi Anak Kota Gorontalo Tinjauan Hukum Pidana dan Fikih Jinayah - Haikal Fikri Ente (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to find out about the forms of child exploitation that occur in the city of Gorontalo and the application of legal sanctions against perpetrators of child exploitation from the perspective of criminal law and jinayah jurisprudence. This research uses empirical legal research methods which are carried out by collecting data through observation and interviews. The results of this research show that the form of child exploitation that occurs in Gorontalo City is sexual exploitation of children. Sexual exploitation of children is the act of using children for sexual purposes in exchange for cash or other forms between children, buyers of sexual services, intermediaries or agents, and other parties who benefit from transactions involving the child's sexuality. In Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection, it is explained that what is meant by sexual exploitation is any form of use of a child's sexual organs or other bodily organs to obtain profit, including but not limited to on all prostitution and obscenity activities as well as in positive criminal law, especially in article 296 of the Criminal Code, it is explained that